Loneliness as Depicted in James Arthur's Empty Space - Ayu Sulistyowati; Ariya Jati (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2023)
This article concerns with loneliness. Loneliness is an unpleasant condition, and the writers are interested in the condition expressed in James Arthurâ€™s â€œEmpty Spaceâ€. The aim of the writing of this article is to describe the loneliness as depicted in the song lyric. The writers focus on the cause of loneliness experienced by the â€œIâ€, and the type of loneliness experienced by the â€œIâ€. The writers use library research to collect data, and they apply a textual analysis to figure out the theme and symbol. The writers adopt the concept of loneliness of Daniel Perlman and Letitia Anne Peplau. The discussion indicates that the cause of the loneliness experienced by â€œIâ€ is the feeling of emptiness when he had lost his lover. Thus, the emergence of this feeling of loneliness is included in the type of emotional loneliness.